2016
DOI: 10.1016/j.contraception.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The safety of intrauterine contraception initiation among women with current asymptomatic cervical infections or at increased risk of sexually transmitted infections

Abstract: Limited evidence suggests that IUD placement does not increase the risk of PID compared with no IUD placement among women with asymptomatic undiagnosed cervical infection or at high risk of STIs. Algorithms based on patient characteristics to identify women with asymptomatic GC/CT may be overly restrictive, leading to missed opportunities for IUD initiation. Historical concerns about higher PID risk among women at risk for STIs who use IUDs may not be relevant with modern devices and STI screening and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Women with current purulent cervicitis or chlamydial infection or gonococcal infection should not undergo IUD insertion (U.S. MEC 4). A systematic review identified two studies that demonstrated no differences in PID rates among women who screened positive for gonorrhea or chlamydia and underwent concurrent IUD insertion compared with women who screened positive and initiated other contraceptive methods (46). Indirect evidence demonstrates women who undergo same-day STD screening and IUD insertion have similar PID rates compared with women who have delayed IUD insertion.…”
Section: Examinations and Tests Needed Before Initiation Of A Cu-iud mentioning
confidence: 99%
“…Women with current purulent cervicitis or chlamydial infection or gonococcal infection should not undergo IUD insertion (U.S. MEC 4). A systematic review identified two studies that demonstrated no differences in PID rates among women who screened positive for gonorrhea or chlamydia and underwent concurrent IUD insertion compared with women who screened positive and initiated other contraceptive methods (46). Indirect evidence demonstrates women who undergo same-day STD screening and IUD insertion have similar PID rates compared with women who have delayed IUD insertion.…”
Section: Examinations and Tests Needed Before Initiation Of A Cu-iud mentioning
confidence: 99%
“…When addressing the safety of LARC methods, one of the concerns regarding copper intrauterine device (IUD) use is the fear of developing pelvic inflammatory disease (PID), and future infertility mainly in young nulliparous women. However, several studies have found that after the first 20 days of insertion, the risk of PID is the same in both users and nonusers (Toivonen et al , 1991; Tsanadis et al , 2002; Lyus et al , 2010; Jatlaoui et al , 2016). Although another study showed that the rate of PID was slightly higher in the IUD group than the non-IUD group (0.46 and 0.09, respectively), the occurrence of PID was rare in both groups (<1.0%) (Birgisson et al , 2015), and the slightly higher rate could be explained by the reduced rate of condom usage in the IUD group.…”
Section: Safety and Effectiveness Of Larc In Lacmentioning
confidence: 99%
“… 24 Conversely, in women with preexisting chlamydial infection, the presence of an IUC was not associated with an increased risk of PID when compared to those women without an IUC. 38 …”
Section: Safetymentioning
confidence: 99%